Psychotropic Medication Effects on Seizure Threshold and Seizure Duration During Electroconvulsive Therapy Stimulus Titration. Issue 2 (June 2020) - Chiao, Stephanie; Isenberg, Keith; North, Carol S.
Abstract : Objectives: Decisions about psychotropic medication administration before electroconvulsive therapy (ECT) are central to management of a very psychiatrically ill patient population. Given that many psychotropic medications are thought to either promote or prevent seizures, there is ongoing concern about concurrent psychotropic medication and ECT administration. This study examined the effect of psychotropic medications on seizure threshold and duration during ECT stimulus titration. Methods: The study sample consisted of 550 patients receiving ECT stimulus titration at a single site during a 27-month period. Systematic chart review provided clinical data, including patients' demographics, psychiatric diagnoses, medications administered in the 48 hours before ECT, and information on the ECT procedure. Referring psychiatrists were advised to discontinue lithium before ECT but otherwise managed psychotropic medications as clinically indicated. A fixed charge titration schedule was used to estimate seizure threshold. Electroconvulsive therapy motor seizure duration was estimated by the cuff method, and electroencephalogram seizure duration was estimated by review of a 2-lead strip. Results: Administration of psychotropic medications, including benzodiazepines, antiepileptics, selective serotonin reuptake inhibitors, tricyclic and tetracyclic antidepressants, bupropion, and stimulants, was not associated with seizure threshold as estimated by electrical charge eliciting a generalized seizure or duration during the initial ECT titration. Tricyclic and tetracyclic antidepressant dosage was associated with seizure threshold. Conclusions: Psychotropic medications may have little effect on seizure threshold and duration during titration of electrical dose at ECT initiation. Integrating this work with other literature supports making recommendations for medication discontinuation before ECT on an individual basis.